2021
DOI: 10.1029/2021jd034574
|View full text |Cite
|
Sign up to set email alerts
|

Ice in Southern Ocean Clouds With Cloud Top Temperatures Exceeding −5°C

Abstract: Climatologies over the Southern Ocean (SO) reveal that more than 80% of the SO is covered by low-level clouds at any given time (e.g., Hu et al., 2010). These clouds are primarily widespread and broken stratocumulus that persist in the cold sectors of extratropical cyclones (Mace et al., 2009). The need to better simulate cloud-radiative processes and constrain the radiative heat budget in cold sectors over the SO, together with the scarcity of in situ measurements of aerosols, clouds, and precipitation to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…The cloud top temperature is higher than −5°C where INP concentrations were previously reported to be the lowest (Kanji et al., 2017), and the liquid/drizzle near cloud base is very likely caused by melting level being located at 1 km above the warm ocean surface. Other studies using satellite observations (Mace, Protat, & Benson, 2021) and airborne observations (Finlon et al., 2020; Zaremba et al., 2021) have also shown possible existence of SIP processes, leading to the high amount of ice over the SO at similar temperature conditions. Several studies mentioned that the warm ocean surfaces over the SO potentially result in stronger updrafts and more turbulence motions, which may be conducive to SIP processes such as rime splintering (Field et al., 2016; Hallett & Mossop, 1974; Korolev & Leisner, 2020; Luke et al., 2021).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The cloud top temperature is higher than −5°C where INP concentrations were previously reported to be the lowest (Kanji et al., 2017), and the liquid/drizzle near cloud base is very likely caused by melting level being located at 1 km above the warm ocean surface. Other studies using satellite observations (Mace, Protat, & Benson, 2021) and airborne observations (Finlon et al., 2020; Zaremba et al., 2021) have also shown possible existence of SIP processes, leading to the high amount of ice over the SO at similar temperature conditions. Several studies mentioned that the warm ocean surfaces over the SO potentially result in stronger updrafts and more turbulence motions, which may be conducive to SIP processes such as rime splintering (Field et al., 2016; Hallett & Mossop, 1974; Korolev & Leisner, 2020; Luke et al., 2021).…”
Section: Discussionmentioning
confidence: 91%
“…In addition to previously reported biases of liquid phase in climate model simulations, several studies have shown that ice phase is likely underestimated in climate model simulations, potentially due to the underestimation of secondary ice production (SIP) processes in model parameterizations (Zhao, Liu, Phillips, et al, 2021;. Other studies using aircraft and satellite observations also indicated that SIP processes likely increase the amount of cloud hydrometeors in ice phase over the SO (Mace, Protat, & Benson, 2021;Zaremba et al, 2021). Several studies evaluated newer versions of climate models with improved representations of SLW in mixed-phase clouds compared with the CMIP5 models and found remaining biases in ice phase.…”
mentioning
confidence: 99%
“…This section discusses methods of identifying cloud phase using both the in situ and remote-sensing data, and compares the identified phases for collocated remote sensing and in situ observations. Detailed information about the in situ and remote probes installed on the NCAR/NSF GV during SOCRATES, their operating characteristics, and the algorithms used to process the data are discussed elsewhere (e.g., D'Alessandro et al, 2021;Järvinen et al, 2022;McFarquhar et al, 2021;Wang et al, 2020;Zaremba et al, 2020Zaremba et al, , 2021. Thus, only a brief summary is provided here together with a focus on unique aspects of the processing required for this analysis.…”
Section: In Situ Datamentioning
confidence: 99%
“…An additional focus was the observation of supercooled liquid water, which is common in the pristine environment of the Southern Ocean (D’Alessandro et al., 2021; Romatschke & Vivekanandan, 2022; Schima et al., 2022). While many of the studies that are based on SOCRATES observations focus on microphysical properties of clouds (D’Alessandro et al., 2021; Efraim et al., 2020; Saliba et al., 2021; Schima et al., 2022; Twohy et al., 2021; Y. Wang et al., 2021; Zaremba et al., 2021; Zhao et al., 2020), few studies (e.g., Truong et al., 2020) have focused on the physical properties of the observed clouds.…”
Section: Introductionmentioning
confidence: 99%
“…While many of the studies that are based on SOCRATES observations focus on microphysical properties of clouds (D'Alessandro et al, 2021;Efraim et al, 2020;Saliba et al, 2021;Schima et al, 2022;Twohy et al, 2021;Y. Wang et al, 2021;Zaremba et al, 2021;Zhao et al, 2020), few studies (e.g., Truong et al, 2020) have focused on the physical properties of the observed clouds.…”
mentioning
confidence: 99%